PENGEMBANGAN ENSIKLOPEDIA MATEMATIKA DALAM AL-QUR’AN UNTUK JENJANG MADRASAH TSANAWIYAH - Almaghfiroh, Violina; Efendy, Muhammad Azrul; Rosyidah, Novia Mar’atur; Abdussakir (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
One of the core competencies expected from students at the Islamic Junior High School level is a spiritual attitude displayed in every subject, including mathematics. Spiritual competence in learning mathematics can be achieved by integrating mathematics with religion, so integrative teaching material references are needed. This research aims to develop an encyclopedia of mathematics in the Qur’an as a valid and practical reference for integrative teaching materials. The method used is research and development with a 4D model (define, design, develop, disseminate). The quality of the product being developed is measured from validity and practicality. The validity aspect is assessed by expert validators, including material, religious, media, and language experts. Meanwhile, the practical aspect is assessed by practitioners. The data collected includes the results of validity and practicality questionnaires and qualitative data in the form of suggestions from validators. The research instruments used were questionnaires of feasibility, practicality, and recommendations or input sheets. This study shows that the average questionnaire score from all experts shows valid criteria with a score of 84.10%. The average questionnaire score from teacher practitioners showed high criteria with a score of 84.37% and student responses showed very high criteria with a score of 85.41%. Based on these results, the developed encyclopedia of mathematics in the Qur’an is valid and practical.